2021
DOI: 10.1002/brb3.2289
|View full text |Cite
|
Sign up to set email alerts
|

Altered behavioral and electrophysiological responses to social fairness in manic and euthymic patients with bipolar disorder

Abstract: Background: Individuals with bipolar disorder show mood instability, including heightened anger and impulsivity. The Ultimatum Game (UG) is a tool used to evaluate emotional and social decision-making strategies. We investigated behavioral and electrophysiological responses to subjectively fair or unfair offers in the UG in patients with bipolar I disorder.Methods: Twenty-four manic patients, 20 euthymic patients, and 30 healthy controls participated in this study. We analyzed their behaviors and collected ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 84 publications
0
2
0
Order By: Relevance
“…Besides bvFTD, the original UG has been used to investigate SDM in different diseases, such as major depression, 18 19 bipolar disorder, 20 21 and schizophrenia. 22 23 Such studies have shown that neuropsychiatric conditions may impact social information processing, and these impairments may be related to biomarker parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Besides bvFTD, the original UG has been used to investigate SDM in different diseases, such as major depression, 18 19 bipolar disorder, 20 21 and schizophrenia. 22 23 Such studies have shown that neuropsychiatric conditions may impact social information processing, and these impairments may be related to biomarker parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Social stability depends on a certain degree of fairness, and if the gap between rich and poor is too wide, society is likely to fall apart ( Ryu et al, 2021 ). However, in the actual distribution of benefits, in the face of the distribution results, there are always members who complain about the unfair distribution and thus denigrate the organization or even quit or turnover, while there are always members who quietly accept and identify with the organization regardless of the distribution.…”
Section: Introductionmentioning
confidence: 99%